(untitled) (CAHIERS MAGELLANES-NS, 2024)
The profound footprint Ambedkar had in shaping today’s India is unparalleled. His impact paved the way for a transformed India with reformed socio-economic structure. His efforts meant for an inclusive idea for the development of Dalits and other weaker sections of the society. Ambedkar had fought for the emancipation of social differences , existing inequalities in caste system throughout his life. He advocated for the education and empowerment of marginalised communities that can develop critical and egalitarian thinking for a better society to evolve . He had a deep faith in giving the labour rights as a meant to ensure social justice and for the annihilation of caste system. While analysing different aspects of Ambedkar’s philosophy , articulation of interaction with Gandhi is quite remarkable. His role in Simon Commission to representing the Depressed classes in Round Table conferences, chairing the drafting committee of Indian constitution manifests his vision for the upliftment of the downtrodden. Ambedkar’s philosophy believes to elaborate that people need a universal moral standard to live in society. His notion of enlightenment entails the ethics of reason is to ensure freedom and equality so as to fraternity can be prevailed in society.